The unwritten law - Ng, See-Yuen; Seasonal Film (Hong Kong : Seasonal Film, 2007)
Story about a low-class prostitute being framed to murder a young, rich businessman, it has voiced the condemn of the grass-root level towards the unfair treatment to them
Title from title scren
Cast: Andy Lau, Deanie Yip
DVD Format
Keywords: Justice -- Law -- Drama; Mothers -- Drama